Algal flora of Betana wetland, Morang, Nepal - Rai, Shiva Kumar (Nepalese Journal of Biosciences, 2013)
In this paper, a total 23 epiphytic as well as planktonic taxa belonging to the classes cyanophyceae (6), chlorophyceae (1) and bacillariophyceae (16) have been enumerated from Betana wetland. Out of these, six diatom taxa viz., Gomphonema constrictum Ehr. var. capitata, Gomphonema intricatum Kütz. var. vibrio, Gomphonema parvulum (Kütz.) var. lagenula Hust., Rhopalodia gibba (Ehr.) O. Müll. var. ventricosa, Nitzschia amphibia Grun. and Surirella tenera Greg. var. ambigua Gandhi were the new records for the country. DOI: http://dx.doi.org/10.3126/njbs.v1i0.7477 Nepalese Journal of Biosciences 1: 104-113 (2011)